Condition of epidermis and epidermal-dermal skin connection in patients with psoriasis and essential hypertension - G. I. Makurina (Patologìâ, 2016)
Background. Issues of lesion pathomorphogenesis in epithelial component of the skin in patients with psoriasis and hypertension on the background of the skin involutive changes requires clarification and further development.